Women in Christian traditions - Moore, Rebecca, 1951- (New York : New York University Press, 2015)
Women in Christian Traditions offers a concise and accessible examination of the roles women have played in the construction and practice of Christian traditions, revealing the enormous debt that this major world religion owes to its female followers. It recovers forgotten and obscured moments in church history to help us to realize a richer and fuller understanding of Christianity. This text provides an overview of the complete sweep of Christian history through the lens of feminist scholarship. Yet it also departs from some of the assumptions of that scholarship, raising questions that challenge our thinking about how women have shaped beliefs and practices during two thousand years of church history. Did the emphasis on virginity in the early church empower Christian women? Did the emphasis on marriage during the Reformations of the sixteenth century improve their status? These questions and others have important implications for women in Christianity in particular, and for women in religion in general, since they go to the heart of the human condition. This work examines themes, movements, and events in their historical contexts and locates churchwomen within the broader developments that have been pivotal in the evolution of Christianity. From the earliest disciples to the latest theologians, from the missionaries to the martyrs, women have been instrumental in keeping the faith alive. Women in Christian Traditions shows how they did so.
Introduction: Why study women in Christian traditions? -- In the beginning ... Eve -- The women disciples in the kingdom of God -- Women and the conversion of an empire -- Saints, seers, and scholars in the Middle Ages -- Women reformed, women resistant -- Spirit-filled women in the nineteenth century -- Churchwomen on the margins and in the mainstream -- Conclusion: The church of Martha and Mary -- Questions for discussion.
Includes bibliographical references (pages 181-196) and index.
Print version record.
Keywords: Women in Christianity -- History; Women in Christianity; Frau; Christentum; Kristendom -- historia; Kyrkligt arbete; Andlighet; Kvinnouppfattning; Feministisk teori; Christianity -- history; Work within the Church; Spirituality; Views of women; Feminist theory; Kvinnor -- religiösa aspekter; RELIGION / Christian Church / History; RELIGION / Christianity / History; History; Electronic books